Synthesis, characterization, antimicrobial activity, and in silico assessment of a novel pyrazoline carboxamide heterocyclic compound - Farouk Boudou; Abdelghani Sehmi; Amal Belakredar; Oussama Zaoui (Bangladesh Pharmacological Society, 2023)
This study presents the synthesis, characterization, and antimicrobial efficacy of a novel pyrazoline carboxamide heterocyclic compound. Synthesized through a two-step process, involving the formation of an α,β-unsaturated ketone and subsequent conversion into a pyrazoline carboxamide derivative, the compound's structure and functional groups were confirmed using FT-IR, 1H NMR, and DEPT-135 techniques. The compound demonstrated high purity and yield, displaying significant inhibitory zones against micro-organisms, notably Listeria monocytogenes (14.2 ± 0.0 mm to 16.8 ± 1.3 mm) and Candida albicans (10.9 ± 0.6 mm to 17.8 ± 1.5 mm). Evaluation of drug-likeness and toxicity highlighted its potential for drug development. Molecular dock-ing studies indicated strong binding affinities to key antimicrobial target proteins, including DNA gyrase, penicillin-binding protein, and C. albicans sterol 14-α-demethylase. Molecular dynamics simulations revealed the com-pound's structural flexibility. These results make this new compound a candidate for further exploration in drug development, highlighting its potential therapeutic applications.